Analisa Yuridis Terhadap Pemberian Keterangan Palsu Dalam Persidangan Oleh Pihak Kepolisian - Husni Thamrin; Ayu Linanda; Mochamad Rifai (LPPM STIH Awang Long, 2021)
False information is essentially a situation where a person gives a false statement on oath (he swears first then strengthened by giving information) or under oath (he gives information first then strengthened by oath), the arrangement on giving false information is contained in book II chapter IX of the Criminal Code entitled Perjury and False Statement and becomes the only article in book II chapter IX of the Criminal Code, i.e. Article 242 of the Criminal Code. In this study examined the false information provided by the police as one component of law enforcement. This research is a normative juridical law research. The technique used in this study is by inventorying primary legal materials, secondary legal materials, and tertiary legal materials, and this type of research uses a statute approach with data analysis methods using qualitative approaches.